Faktor-Faktor yang Memengaruhi Kesulitan Belajar IPS di MTs Swasta Darul Ulum Budi Agung Kota Medan - Amini, Amini; Simamora, Sari Kurniah; Dawani, Syafitri Revi; Zanisti, Haryati; Ratih, Sasika; Maskuri. S, M. Irham (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Studying is someone's effort to change behavior as a whole. The teacher's ability to use learning media aims to make students active and easily absorb the material. The learning process is not always smooth, there are several obstacles that make students often experience difficulties, including in learning Social Studies at Darul Ulum Budi Agung Private MTs, Medan City. This study aims to determine the factors that affect students' difficulties in learning Social Studies with a qualitative research method. The results show that there are two factors that influence, namely internal factors such as students' interest in learning and the effectiveness of teachers in making the learning process interesting, as well as external factors such as the role of parents in controlling students' learning at home.